2012
DOI: 10.2190/pm.44.3.d
|View full text |Cite
|
Sign up to set email alerts
|

Hypohidrotic Ectodermal Dysplasia: A Multidisciplinary Approach

Abstract: Hypohidrotic ectodermal dysplasia (HED; Christ-Siemens-Touraine syndrome) is a genetic disorder characterized by sparse hair, oligodontia with peg-shaped teeth, reduced sweating, and defects in a number of other ectodermal organs. A partial or complete absence of eccrine glands can lead to recurrent severe overheating that may cause seizures and neurological deficits. This clinical report presents a 14-year-old male patient with hypohidrotic ectodermal dysplasia, including the clinical and radiographic finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…In total, 146 individuals (119 male; 27 female) diagnosed with HED were included in the present systematic review. The diagnosis (XL)HED was established clinically by the presence of hypo‐ or anhidrosis, hypotrichosis, hypo‐ or anodontia, and typical craniofacial dysmorphologies, with or without a positive family history or other tests such as skin biopsy (n = 6), dermatoglyphic findings (n = 3), microscopic sweat pore counts in vivo (n = 1) or starch‐iodine test (n = 1) . The clinical diagnosis of (XL)HED was reported as genetically confirmed in 29 male individuals .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 146 individuals (119 male; 27 female) diagnosed with HED were included in the present systematic review. The diagnosis (XL)HED was established clinically by the presence of hypo‐ or anhidrosis, hypotrichosis, hypo‐ or anodontia, and typical craniofacial dysmorphologies, with or without a positive family history or other tests such as skin biopsy (n = 6), dermatoglyphic findings (n = 3), microscopic sweat pore counts in vivo (n = 1) or starch‐iodine test (n = 1) . The clinical diagnosis of (XL)HED was reported as genetically confirmed in 29 male individuals .…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen case reports and two case series reported on prosthetic rehabilitation of 17 teenagers (13 males, 4 females) aged 10‐17 years with HED (Table ). At the time of prosthetic rehabilitation, teenagers were 13 (10/16.4) years.…”
Section: Resultsmentioning
confidence: 99%
“…HED seriously affects physical and mental health of patients and brings heavy economic burdens to family and society. In the past, the main treatments of HED were symptomatic approaches, including avoiding high temperature, prosthetic treatment, psychological treatment, and speech therapy to improve life quality of patients (Bildik et al, 2012; Ding et al, 2020; Schnabl et al, 2018). Fortunately, in 2018, Schneider treated three affected human fetuses through the intra‐amniotic delivery of a fusion protein that substitutes for the function of the affected EDA1 protein (Schneider et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The desire for better aesthetics and comfort directly reflects on the motivation to undergo extensive surgery in this age group. [29][30][31] A removable dental prosthesis remains more feasible alternative compared to fixed teeth-supported or implant-supported prostheses because the removable prosthesis is less invasive, more affordable, and it is easier to maintain oral hygiene. [38] Swelem et al, [21] reported on patient satisfaction, and quality of life assessment among removable dental prosthesis wearers suggested that comfort, general satisfaction, and masticatory efficiency were significantly higher after conventional treatment and continued to improve significantly after the use of attachments.…”
Section: Discussionmentioning
confidence: 99%